Study on the system of a capsule endoscope driven by an outer rotational magnetic field - Zhang, Wei; Chen, Yingjun; Huang, Ping (2006 2nd IEEE/ASME International Conference on Mechatronics and Embedded Systems and Applications, 2006)
The system studied in this paper consists of a capsule endoscope and an external system. The exterior of the capsule endoscope is a spiral surface with a pair of magnetic bars. Inside the CE, there are an optical system, a CMOS image sensor and its circuit, a power supply, a power control circuit, and a radio transmitting circuit. The external system produces a rotational magnetic field and contains several main parts: three fixed magnet resistance transducers, two pairs of electromagnetic coils at every other 90deg, the basement of the electromagnetic coils and tracks, a control circuit, and a scheduling circuit. The magnet resistance transducers track the movement of the capsule endoscope and the electromagnetic coils control it to move forward and backward for the purpose of observation. A tester is set up to simulate the action of a rotating magnetic field and three capsule endoscope samples with a spiral surface are fabricated to perform the functions of imaging and delivering. Then, experiments that the samples move in off-body pig intestine are carried out. It is found that when the intensity of the outer magnetic field is about 500 Oe, the active torque on the samples is about 1.0 mN.m. When the diameter of the samples is less than 20 mm, the capsule endoscope can move normally in off-body pig intestine under the outer rotational magnetic field